2012
DOI: 10.1371/journal.pone.0042370
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to MHC Class II Molecules Induce Autoimmunity: Critical Role for Macrophages in the Immunopathogenesis of Obliterative Airway Disease

Abstract: Previous studies have shown that intrabronchial administration of antibodies (Abs) to MHC class I resulted in development of obliterative airway disease (OAD), a correlate of chronic human lung allograft rejection. Since development of Abs specific to mismatched donor HLA class II have also been associated with chronic human lung allograft rejection, we analyzed the role of Abs to MHC class II in inducing OAD. Administration of MHC class II Abs (M5/114) to C57BL/6 mice induced the classical features of OAD eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…A number of studies have suggested possible mechanistic effects of HLA-specific antibodies in the development of obstructive airway disease. [37][38][39][40][41] The majority of these studies utilized W6/32, a monoclonal antibody directed against a monomorphic determinant on HLA Class I molecules. Ligation of W6/32 to epithelial cells has been shown to cause cell proliferation, production of growth factors and chemotactic factors, as well as cell death through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested possible mechanistic effects of HLA-specific antibodies in the development of obstructive airway disease. [37][38][39][40][41] The majority of these studies utilized W6/32, a monoclonal antibody directed against a monomorphic determinant on HLA Class I molecules. Ligation of W6/32 to epithelial cells has been shown to cause cell proliferation, production of growth factors and chemotactic factors, as well as cell death through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of DSA detected after lung transplantation are directed against HLA Class II molecules. A recent study by Takenaka et al 41 demonstrated that administration of a monoclonal antibody to Class II antigens led to the development of obstructive airway disease in a mouse model. Further work is required to understand the effects of antibodies to Class II antigens on epithelial cells and development of BOS.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms of AMR are not firmly established, de novo donor-specific antibodies against HLA have been shown to predispose to the development of immune responses to lung self-antigens and BOS (69)(70)(71). To define mechanisms leading to anti-MHC-mediated development of rejection, a preclinical murine model was developed in which exogenous anti-MHC was administered into the native lungs and elicited production of antibodies and T cell responses specific for lung-associated self-antigens, type V collagen [col(V)], and K-α 1 tubulin, culminating in fibrotic pathology (72,73). Human lung transplant recipients develop antibodies against col(V), a protein mainly located in the lung interstitium and not ordinarily exposed to the immune system.…”
Section: Armentioning
confidence: 99%
“…The infiltration of activated macrophages in liver tissue was assessed by immunohistochemistry staining of established macrophage markers, including F4/80 for mature macrophages, CD11C for classically activated (M1) macrophages, and CD206 for alternatively activated (M2) macrophages (6,21,50) to illustrate the hepatic inflammation response to diabetic pathology (27). Immunohistochemistry was performed as usual (63).…”
Section: Spontaneous Voluntary Activitymentioning
confidence: 99%